1993
DOI: 10.1111/j.1432-1033.1993.tb19880.x
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin‐induced lipid peroxidation and glutathione peroxidase activity in tumor cell lines selected for resistance to doxorubicin

Abstract: Doxorubicin‐induced lipid peroxidation was evaluated in four human or murine cell strains in culture and in their doxorubicin‐resistant variants, by the quantification of malondialdehyde produced after a 2‐h incubation of cells with the drug. Significantly increased malondialdehyde levels were obtained 24 h after doxorubicin treatment in three of the wild‐type cell lines with doses as low as 0.05–0.1 μg/ml, which is within an order of magnitude of the concentration of the drug which inhibits cell growth by 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 26 publications
2
24
0
1
Order By: Relevance
“…24,25) Thus, we examined the effects of citrulline using LPO as an indicator of DOX cardiotoxicity, and observed significant inhibition of DOX-induced LPO accumulation in the heart. It is suggested that these effects were related to antioxidant activities, involving scavenging of hydroxyl radicals by citrulline.…”
Section: Discussionmentioning
confidence: 99%
“…24,25) Thus, we examined the effects of citrulline using LPO as an indicator of DOX cardiotoxicity, and observed significant inhibition of DOX-induced LPO accumulation in the heart. It is suggested that these effects were related to antioxidant activities, involving scavenging of hydroxyl radicals by citrulline.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the liver has higher cytochrome-P450 reductase level than does cardiac tissue (Myers et al 1982). The semiquinone subsequently reacts with oxygen, iron, and hydrogen peroxide to produce ROS causing apoptosis and cell damage (Benchekroun et al 1993;Chen et al 2013). Therefore, oxidative stress induced in rat liver by ADR was found to be higher than in the controls in our current study.…”
Section: Discussionmentioning
confidence: 44%
“…*p \ 0.05 versus ADR. All data were expressed as mean ± SEM mitochondria electron transport system (Chen et al 2013) from mainly cytochrome-P450 reductase enzyme (Benchekroun et al 1993) which is important for the metabolism of both endogenous (e.g. lipids, steroids) and exogenous (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation with radical scavengers caused cell viability to return to the baseline level of doxorubicin in the absence of polyunsaturated fatty acids (Germain et al, 1998). Moreover, in a doxorubicin-resistant mammary tumour cell line, lipid peroxidation levels were found to be lower than in the wild-type cell line (Benchekroun et al, 1993). These data point towards the notion that lipid peroxidation may be a general mechanism by which the permeability of tumour cell membranes may be increased for doxorubicin and its anthracycline derivatives.…”
Section: mentioning
confidence: 88%